Polycystic ovary syndrome : challenging issues in the modern era of individualized medicine - Diamanti-Kandarakis, Evanthia (Elsevier, 2022)
Women's healthcare regarding polycystic ovarian syndrome remains challenging. Patients often go from one specialist to another trying to fully understand and management the disorder. Women often go years before a diagnosis, seeing three or more doctors before a confirmed diagnosis. Polycystic Ovarian Syndrome: Challenging Issues in the Modern Era of Individualized Medicine brings together multiple medical disciplines to improve the care of women with PCOS. Such a multidisciplinary clinical and scientific approach integrates obstetrics and gynecology, pediatric and medical endocrinology, internal medicine, genetics, psychology and laboratory medicine into relevant translational clinical and scientific discussions that update both the scientific understanding of PCOS and the diagnosis and management of all aspects of the syndrome. The impact of PCO on the onset of puberty is subdivided in sub sections to get a better understanding of this condition and the management at different stages in a woman's life.